Interactions in psychosocial interventions in dementia care: A systematic review protocol - Ivy Meihua Su; Keyu Li; Winsy Wing Sze Wong (PLoS ONE, 2026)
Background Psychosocial interventions are regarded as preferable in dementia care, as they have been tested as effective in preserving people living with dementia’s function, reducing stress, and enhancing well-being. Typically delivered in structural activities, these interventions feature psychosocial, environmental, and behavioral interactions with people living with dementia. The degree and patterns of people living with dementia’s interactional behaviors, therefore, indicate their engagement and participation in the intervention and may have an impact on the effect of psychosocial therapies. Objective The systematic review aims to 1) synthesize the empirical evidence of measurement tools used to measure interactions in psychosocial interventions across various therapeutic settings and 2) investigate whether existing studies have investigated the relationship between measures of interaction and treatment outcomes, if yes, further investigation will be carried out to describe the relationship between measures and outcomes. Empirical studies and psychometric studies of scales are eligible for inclusion. Methods The study protocol has been registered at the Campbell Systematic Reviews (cl2.20250120). Search will be conducted on PubMed, PsycINFO (ProQuest), MedLine (EbscoHost), CINAHL (EbscoHost), and Cochrane Library from inception until December 31, 2025, for studies measuring people living with dementia’s interactions in psychosocial interventions. The inclusion of studies will involve two independent reviewers through a two-phase procedure. During the first phase, reviewers will assess titles and abstracts, which will be followed by reading the full texts employing the predefined eligibility criteria. Data extracted will include study nature/characteristics, aspects of interactions measured, measurement methods, and the relation to outcomes. The risk of bias will be assessed using the Quality Assessment Tool for Quantitative Studies for quantitative studies and the Critical Appraisal Skills Programme (CASP) checklist for qualitative studies. Results will be synthesized into a descriptive analysis, given the results of the included literature. Importance This systematic review will enable a comprehensive analysis of existing frameworks used to measure interactions in psychosocial interventions across diverse settings. It may contribute to the effective measurement of interactions and provide insights into the quantitative analysis of the relation between interaction and outcome measures.